2003
DOI: 10.4049/jimmunol.170.8.4053
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the NF-κB Target Gene X-Ray-Inducible Immediate Early Response Factor-1 Short Enhances TNF-α-Induced Hepatocyte Apoptosis by Inhibiting Akt Activation

Abstract: Using a cDNA microarray analysis, we identified x-ray-inducible immediate early response factor-1 (IEX-1) as a proapoptotic gene which was induced by TNF-α and also depend on NF-κB activation in Hc human hepatocytes. In these cells only the original form of IEX-1, termed IEX-1S, but not its longer transcript IEX-1L, was expressed. Overexpression of IEX-1S resulted in promotion of TNF-α-induced apoptosis in Hc cells expressing a mutant form of IκB. This proapoptotic action can be explained by its inhibitory fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 46 publications
7
57
1
Order By: Relevance
“…IEX-1 as well as its rodent homologues PRG1 and gly96 represent short-lived proteins consisting of 156, 160 and 153 amino acids, respectively, and, to current knowledge, share no significant sequence similarities with any other known protein. Depending on cell type and stimulus-specific conditions, IEX-1 regulates cell growth and cellular viability (reviewed in Wu, 2003), and a significant apoptosis triggering effect by IEX-1 has been described (Scha¨fer et al, 1999;Arlt et al, 2001;Grobe et al, 2001;Schilling et al, 2001;Osawa et al, 2003;Shen et al, 2006). In the present study, we identified IEX-1 as an important mediator of G17-dependent NFkB inhibition and apoptosis in Colo320 cells expressing the wild-type CCK2 receptor.…”
Section: Introductionsupporting
confidence: 51%
“…IEX-1 as well as its rodent homologues PRG1 and gly96 represent short-lived proteins consisting of 156, 160 and 153 amino acids, respectively, and, to current knowledge, share no significant sequence similarities with any other known protein. Depending on cell type and stimulus-specific conditions, IEX-1 regulates cell growth and cellular viability (reviewed in Wu, 2003), and a significant apoptosis triggering effect by IEX-1 has been described (Scha¨fer et al, 1999;Arlt et al, 2001;Grobe et al, 2001;Schilling et al, 2001;Osawa et al, 2003;Shen et al, 2006). In the present study, we identified IEX-1 as an important mediator of G17-dependent NFkB inhibition and apoptosis in Colo320 cells expressing the wild-type CCK2 receptor.…”
Section: Introductionsupporting
confidence: 51%
“…IEX-1 enhances apoptosis in some cells, whereas in other cell systems, IEX-1 protects against apoptosis [7,8,[11][12][13]19,22,23]. Our findings show that IEX-1 may function in the control of apoptosis by directly binding to a variety of proteins associated with either the enhancement or inhibition of apoptosis and that differential binding and activation may provide an explanation for the varied effects of this protein in different cells.…”
Section: Resultsmentioning
confidence: 85%
“…The human immediate early gene X-1 (IEX-1, also known as Dif2, and murine orthologs gly96 and PRG1) plays a role in the control of apoptosis and cellular growth [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The gene (gly96) was initially identified in mouse fibroblasts as a serum-regulated, glycosylated, immediate early gene [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations